THE ETHNO-CULTURAL COMPONENT IN THE ADVERTISING TEXTS OF EDUCATIONAL ORGANISATIONS IN FOREIGN LANGUAGE EDUCATION - E.V. Biryukova; N.S. Parshkov (Многоязычие в образовательном пространстве)
As is known, modern transformations in the field of education have lead to increased competition in this area. In order to increase competitiveness, educational organisations use the latest means and methods of advertising promotion. The relevance of the research is justified by the dependence of the features of an advertising text on the ethnocultural specifics of the advertisement target audience. The object of the study is the ethnocultural component in the advertising texts of educational organisations. The advertising texts of the Moscow City University on the social network VKontakte are the subject of the study. The purpose of the study is to identify and clarify the functioning of the ethnocultural component in the advertising texts of educational organisations. To achieve this goal, the content of the ethnocultural component as a linguistic structure and the features of the advertising promotion of educational organisations were described and analysed. In the course of the study, we applied such theoretical research methods as the analysis of scientific literature on the research topic and advertising texts of the Moscow City University on the social network VKontakte, systematisation and generalisation of the obtained information. Empirical research methods are represented by such a method as observation. As a result of the conducted analysis, the implicit inclusion of an ethnocultural component as a reference to cultural realities and precedent phenomena in texts related to both the culture of the countries of the studied languages and the culture of the native country were revealed, and the structure of the analysed texts corresponded to the speech behaviour of the target audience.